2022
DOI: 10.1111/aji.13625
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal SARS‐CoV‐2 vaccination and first trimester infection on feto‐maternal immune responses

Abstract: Problem COVID‐19 infection during pregnancy increases maternal and fetal morbidity and mortality. Infection in the second or third trimester leads to changes in the decidual leukocyte populations. However, it is not known whether COVID‐19 infection in the first trimester or COVID‐19 vaccination during pregnancy alters the decidual immune environment. Method of study We examined decidual biopsies obtained at delivery from women who had COVID‐19 in the first trimester ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…Given that most pregnant individuals in our study received vaccinations months prior to delivery, it is likely that any transient elevation in IP-10 or IFN-γ after vaccination declined to baseline levels by the time of delivery. This would be consistent with our prior study of decidual placental tissue from vaccinated versus control pregnancies which demonstrated lower levels of macrophages and natural killer cells in the vaccinated group ( Juttukonda et al, 2022 ).…”
Section: Resultssupporting
confidence: 92%
“…Given that most pregnant individuals in our study received vaccinations months prior to delivery, it is likely that any transient elevation in IP-10 or IFN-γ after vaccination declined to baseline levels by the time of delivery. This would be consistent with our prior study of decidual placental tissue from vaccinated versus control pregnancies which demonstrated lower levels of macrophages and natural killer cells in the vaccinated group ( Juttukonda et al, 2022 ).…”
Section: Resultssupporting
confidence: 92%
“…Sixteen performed adjusted analysis for pregnancy-related maternal and offspring outcomes (544 314 women) 22–37. We included 16 studies (425 867 women) reporting SARS-CoV-2 infection-related outcomes6 7 17 19 21 31 33 36 38–45 and 35 (1 362 172 women) reporting pregnancy-related maternal and offspring outcomes in the secondary analysis 17 18 21–24 29–34 36 38 39 41–60. Twenty-three studies reported reactogenicity outcomes (94 206 women) following vaccination 38 39 46 61–80…”
Section: Resultsmentioning
confidence: 99%
“…Studies evaluating how decidual leukocytes are altered by maternal SARS-CoV-2 infection during gestations are inconsistent. Early reports suggested that COVID-19 infection in the first trimester did not alter leukocyte frequencies within the decidua 92 . Other studies have demonstrated increased macrophages, NK cells, and T cells, accompanied by elevated expression of various cytokines (IL-6, IL-8, IL-10, TNFα) with maternal SARS-CoV-2 infection in the first trimester 92,93 .…”
Section: Maternal Sars-cov-2 Infection Has Been Shown To Compromise P...mentioning
confidence: 98%
“…Early reports suggested that COVID-19 infection in the first trimester did not alter leukocyte frequencies within the decidua 92 . Other studies have demonstrated increased macrophages, NK cells, and T cells, accompanied by elevated expression of various cytokines (IL-6, IL-8, IL-10, TNFα) with maternal SARS-CoV-2 infection in the first trimester 92,93 . Our previous studies show significant perturbations induced by maternal SARS-CoV-2 infection in the decidua 12,38 , including attenuated antigen presentation and viral signaling pathways, reduced frequencies of tissue-resident decidual macrophages, and upregulated cytokine/chemokine signaling in monocyte-derived decidual macrophages 12,38 .…”
Section: Maternal Sars-cov-2 Infection Has Been Shown To Compromise P...mentioning
confidence: 98%